2005
DOI: 10.1111/j.1365-2133.2005.06760.x
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of clonality for the detection of cases clinically and/or histopathologically not recognized as cutaneous T-cell lymphoma

Abstract: The study showed that the PCR-heteroduplex technique can determine a high percentage of monoclonality only in plaque stage MF. However, in spite of the low sensitivity of the method, several cases previously unrecognized could be reclassified as MF when their clinical and histopathological features were re-evaluated taking into account the clonality of the lymphocytic infiltrate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
14
1
Order By: Relevance
“…32,33 This is exemplified by the results of TCR gene rearrangement studies in MF and benign inflammatory dermatoses which may mimic MF. Early patchstage MF frequently lacks a detectable clonal rearrangement, 34 and benign inflammatory dermatoses occasionally have a clonal rearrangement. 34,35 This emphasizes the need for clinicopathologic correlation when interpreting the results of clonality studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 This is exemplified by the results of TCR gene rearrangement studies in MF and benign inflammatory dermatoses which may mimic MF. Early patchstage MF frequently lacks a detectable clonal rearrangement, 34 and benign inflammatory dermatoses occasionally have a clonal rearrangement. 34,35 This emphasizes the need for clinicopathologic correlation when interpreting the results of clonality studies.…”
Section: Resultsmentioning
confidence: 99%
“…Early patchstage MF frequently lacks a detectable clonal rearrangement, 34 and benign inflammatory dermatoses occasionally have a clonal rearrangement. 34,35 This emphasizes the need for clinicopathologic correlation when interpreting the results of clonality studies. While several authors have suggested evolving histologic criteria for the diagnosis of cutaneous T-cell lymphoma over the past several years, [36][37][38][39] ultimately, clinicopathologic correlation is essential when differentiating MF from its histologic mimickers.…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity is even comparable and at times greater than results of single biopsy studies where the presence of a dominant Tcell clone has been reported in a percentage of patients with CTCL ranging from 40% to 90%. 13,14 In a recent single biopsy study including 36 patients with MF, Alessi et al, 20 using a PCR-HD technique, found the sensitivity of TCRg clonality to be 50%. More specifically, a TCRg clonal rearrangement was found in 14 of 16 (87.5%) cases clinically and histopathologically classified as plaque-stage MF and in 4 of 20 cases (20%) clinically and histopathologically classified as patch-stage MF.…”
Section: Discussionmentioning
confidence: 98%
“…3 MF progresses through different clinical stages, which are classified according to the tumornode-metastases (TNM) system for cutaneous lymphomas. 4 Although there is evidence of transformation in the initial stages, [5][6][7] the lesions can persist for many years and present as a chronic skin disease. 8,9 Therefore, it is possible that the characteristics of the CD4 1 T cells in the early skin lesions of MF patients play an important role in the outcome of the disease.…”
Section: Mycosis Fungoides (Mf) Is the Most Common Clinical Variant Omentioning
confidence: 99%